Exploring the Role of Derivational Affixes through Marvel Studios' Doctor Strange in the Multiverse of Madness Playlist on YouTube - Meira Nuha Maulida (Syntax Idea)
This research was conducted with the aim of identifying the affix derivational process and understanding the position of word meaning in a spectacle through Marvel Studios' Doctor Strange in the Multiverse of Madness Playlist on Youtube. Descriptive qualitative is used as the research method with morphology as the approach. Data collection is done by sorting the data based on the affix derivational process. Through this research, 71 data points were obtained in the form of 5 prefixes and 66 suffixes with 11 types of word class changes. The suffixes -ing and -ed are the most common in the video playlist, with adjective to adjective as the most common word class found. The use of these derivational affixes contributes to word renewal as well as expanding word class changes.